Proses Ekspor PT. Ragam Rasa Raya - Maria Elisabeth Jessica Santoso; Ni Putu Agnes P.W; Obaja Elka Kurniawan; Radella Revana; Rafael Alvin; Roland Satrya Budiman (Journal of the Community Development in Asia (JCDA), 2018)
Startegy that we use is targeting places that that our competitors didn’t reach yet. Instead reach a new market place, we also want to reach our vision, that is being the number one cigarettes in Indonesia. So we trying to introduce our product in Indonesian start in village and year years after that we are good enough and strong enugh to compete with our competitors in bigger place. We trying to make the best cigarettes and make a interest taste to our customer, that is gonna make our customer stay using our product , so our customer not trying to look at competitors product. The way we did to make the best cigarettes is strict selection to our raw materials, that is tobacco. We have strict selection for tobacco that we can use to our cigarettes. PT. Ragam Rasa Raya has stable finance capability and this company choose L/C or Letter of Credit for paying method. So that prove that this company good enough for export their product. PT. Ragam Rasa Raya supported by a good human resource management, we can see from the way that this company classificating the type of the workers. We need 6 workers, two for truck drivers, one person for take in charge and accountable of forklift, one person to manage load the stuff, and 2 left for holding the stuff from the storage.